Interview with Stepwise Sironko early adopter farmer - Mr. Antonina Mateba - Margiotta, S. (International Institute of Tropical Agriculture, 2019)
Interview with Stepwise Sironko early adopter Ms. Antonina Mateba sharing her experience on what inspired her to adopt some of the climate smart agricultural practices under Stepwise.